Contemporary approach to the surgical management of traumatic submacular hemorrhage with choroidal rupture (case series) - A.V. Seleznev; U.L. Amashova; A.Yu. Brezhnev; Z.M. Nagornova; A.C. Egorova; A.V. Kuroyedov (РМЖ "Клиническая офтальмология")
A.V. Seleznev1,2, U.L. Amashova1, A.Yu. Brezhnev3, Z.M. Nagornova1, A.C. Egorova1, A.V. Kuroyedov4,5 1Ivanovo State Medical Academy, Ivanovo, Russian Federation 2Ivanovo Regional Clinical Hospital, Ivanovo, Russian Federation 3Kursk State Medical University, Kursk, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation 5P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation The selection of management strategy for closed globe injury with massive submacular hemorrhage (SMH) remains a pertinent issue, particularly in the context of the advent and improvement of surgical techniques. These patients typically maintain an active lifestyle and are highly demanding with regard to vision. Moreover, existing observational approaches and passive management of SMH are unacceptable for them. This paper describes two patients with closed globe injuries accompanied by SMH and significant vision loss. The active management strategy employed for these patients (pneumodislocation plus enzymatic lysis) was analyzed based on the results of optical coherence tomography, eye fundus photography, and visual acuity measurement. The intravitreal injection of drugs and a gas-air mixture resulted in a significant improvement of visual acuity due to the displacement of the subretinal blood clot to the extramacular area, reduction in the height and area of hemorrhage, and elimination of the toxic effect of blood elements on the retinal pigment epithelium and photoreceptors. This management strategy for SMH helps improve vision in a short time interval and to reduce potential negative effects of this condition. Keywords: subretinal hemorrhage, closed globe injury, choroidal rupture, intravitreal injection, tissue plasminogen activator, commotio retinae. For citation: Seleznev A.V., Amashova U.L., Brezhnev A.Yu., Nagornova Z.M., Egorova A.C., Kuroyedov A.V. Contemporary approach to the surgical management of traumatic submacular hemorrhage with choroidal rupture (case series). Russian Journal of Clinical Ophthalmology. 2024;24(2):94–100 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-9.